Does the Netherlands comply with national law and Article 2 of human rights concerning deceased minors? - Sophie C. T. van Rhenen; Tess M. Wemeijer; Cédrique A. S. Gregoire; Wilma L. J. M. Duijst (PLoS ONE, 2025)
Background In the Netherlands, reporting the death of a minor to a forensic physician has been legally required since 2010. Additionally, the Postmortem Evaluation of Sudden Death in Youth (PESUDY) procedure can be initiated for unexplained natural deaths. Objective This study assesses the reporting rate of deceased minors to forensic physicians, evaluates PESUDY submission rates, and explores reasons for declining PESUDY, under the European Convention on Human Rights (ECHR) and the Convention on the Rights of the Child (CRC) obligations. Participants and setting This observational, retrospective study examined data on deceased minors in the Netherlands in 2022 and 2023. Methods Data were collected from forensic registration databases, the Central Bureau of Statistics (CBS) and the PESUDY scientific committee. PESUDY submission rates were analyzed, along with reasons for declining the procedure. Results The reporting rate of deceased minors to forensic physicians represented 69% in 2022 and 68% in 2023. The reporting rates for perinatal deaths and deaths outside this period were 47% and 96% in 2022, and 57% and 83% in 2023, respectively. The submission rate of PESUDY-eligible cases was 66% in 2022 and 68% in 2023. The reasons for not pursuing PESUDY were parental refusal without explanation (nine cases), and religious reasons (three cases). In 40 cases, there were no reasons documented. Conclusions The reporting of deceased minors is not adhered to, with stagnating reporting rates. Additionally, the need for parental consent for post-mortem investigations hinders thorough examination, potentially obscuring cases of child abuse. This brings about nonconformity with the ECHR and CRC on the right to life.